BEYOND FREUD AND BEHAVIORISM: SUFISM AS THE ROOT OF TRANSPERSONAL PSYCHOLOGY IN UNDERSTANDING HUMAN CONSCIOUSNESS - Anggraini, Leli; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
This article aims to analyze the position of Sufism as an often overlooked intellectual and practical foundation in the birth of Transpersonal Psychology. Through a literature study and comparative analysis approach, this research criticizes the limitations of mainstream psychological paradigms—particularly Freudian Psychoanalysis and Behaviorism—which fail to explain the spiritual dimension and peak experiences of humans. The research findings show that key concepts of Sufism such as fana ' (destruction of the ego ), ma'rifat(divine knowledge), andZikr as a method of developing consciousness, has been discussing the